1987
DOI: 10.1039/p29870000371
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance studies. Part 71. Side-chain oxidation pathways in the reactions of ˙OH and SO4˙ with some phenyl-substituted carboxylic acids, their anions, and some related compounds

Abstract: A series of arene radical-cations has been generated in situ by the reactions of methylbenzene, phenylethanoic acid, 3-phenylpropanoic acid, and some derivatives and cyclic analogues with both SO4-* and *OH (the latter in acid solution). The results are interpreted in terms of a variety of subsequent rapid reactions including hydration, deprotonation (to give benzylic radicals), and fragmentation (decarboxylation): for a series of radical-zwitterions +'Ar( CH,),CO;( n = 1-3) decarboxylation (k 3 lo9 dm3 mo1-l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…For nonbenzophenone type 2-arylacetic acids, i.e., phenylacetic acids lacking an aroyl substituent, a different decarboxylation pathway is operative. Previous spectroscopic studies have shown that phenylacetic acids undergo fragmentation in aqueous media upon addition of sulfate radical anions or hydroxyl radicals as well as upon direct biphotonic ionization at λ = 248 nm, thus yielding benzyl radicals. This radical pathway was further confirmed in earlier studies on the photoinduced electron transfer (PET) of phenylacetic acids with acridine. , …”
Section: Introductionmentioning
confidence: 67%
“…For nonbenzophenone type 2-arylacetic acids, i.e., phenylacetic acids lacking an aroyl substituent, a different decarboxylation pathway is operative. Previous spectroscopic studies have shown that phenylacetic acids undergo fragmentation in aqueous media upon addition of sulfate radical anions or hydroxyl radicals as well as upon direct biphotonic ionization at λ = 248 nm, thus yielding benzyl radicals. This radical pathway was further confirmed in earlier studies on the photoinduced electron transfer (PET) of phenylacetic acids with acridine. , …”
Section: Introductionmentioning
confidence: 67%
“…Precedent for such an internal SET exists; the research group of Young reported that during the reaction of SO 4 .− and a series of phenyl-substituted carboxylic acids an electron transfer took place from the carboxylate functional group to an aromatic radical cation or an intermediate species. [ 54 ]…”
Section: Resultsmentioning
confidence: 99%
“…The dimer radical-cation expectedt7 to result from the reaction of the radical-cation with parent, was directly detected in experiments in which the photomultiplier was replaced as a detector by a photodiode (to provide the greater sensitivity needed to detect absorptions at higher wavelength, e.g. 1 100 nm, see Figure 6). The broad band at CQ.…”
Section: Resultsmentioning
confidence: 99%